Tell me how it ends: an essay in 40 questions ebook - Luiselli, Valeria (2017)
American Book Award Winner: A "moving, intimate" account of serving as a translator for undocumented children facing deportation ( The New York Times Book Review ). Nonfiction Finalist for the Kirkus Prize Finalist for National Book Critics Circle Award for Criticism Structured around the forty questions volunteer worker Valeria Luiselli translates from a court system form and asks undocumented Latin American children facing deportation, Tell Me How It Ends humanizes these young migrants and highlights the contradiction between the idea of America as a fiction for immigrants and the reality of racism and fear—here and back home. "Luiselli's prose is always lush and astute, but this long essay, which borrows its framework from questions on the cold, bureaucratic work sheets with which she became so familiar (for example, 'Did anything happen on your trip to the U.S. that scared or hurt you?'), is teeming with urgency...In this slim volume about the spectacular failure of the American Dream, she tells the stories of the unnamed children she's encountered and their fears and desires, as well as her own family's immigration story." — Vulture "Worthy of inclusion in a great American (and international) canon of writing about migration." – Texas Observer "A powerful indictment of American immigration policy, [ Tell Me How It Ends ] examines a system that has failed child refugees in particular." —Financial Times "Masterfully blends journalism, auto/biography, and political history into a compelling and cohesive narrative. . . . Luiselli uses the personal to get political but smartly sidesteps identity politics to focus on policy instead."— The Rumpus